Combining social protection interventions for better food security: Evidence from female-headed households in Amhara region, Ethiopia. - Essa Chanie Mussa; Dessie Agegnehu; Emmanuel Nshakira-Rukundo (PLoS ONE, 2024)
Ethiopia introduced its flagship poverty-targeted social protection program, the Productive safety net program (PSNP), in 2005 and Community-Based Health Insurance (CBHI) in 2011. Although both programs operate in several districts with some overlaps, evidence is scarce on how these large-scale programs jointly affect the food security of vulnerable groups. This study examines the impacts of a combination of these programs on food security outcomes among female-headed households in a chronically food-insecure and drought-prone district. Cross-sectional data were collected from 365 female-headed households selected through multi-stage sampling technique and analyzed using Inverse-probability-weighted regression adjustment (IPWRA) strategy to assess the effect of the programs on food security. The results show that while 63.6% of sample households are enrolled in CBHI and 48.8% are beneficiaries of PSNP's conditional cash transfer (CCT) component, membership in both social protection programs was 38.9%. The IPWRA analysis finds that inclusion in the CCT combined with CBHI, on average, increased dietary diversity score by 0.918 (95% CI 0.779-1.057) and food consumption score by 0.576 (95% CI 0.464-0.688). It also reduced household food insecurity access scale by 8.658 (95% CI -9.775 - -7.541). In all assessments, a combination of CBHI and CCT always produced results of a larger magnitude than each of CBHI and CCT alone. The findings provide evidence of the potentials of integrating social protection programs to increase food security outcomes among the most vulnerable and marginalized groups in a developing country. In addition, the results have also useful implications to achieve sustainable development goals related to ending hunger and achieving food security among vulnerable groups.